Metabolic syndrome reduces the contribution of K(+) channels to ischemic coronary vasodilation - Borbouse, Léna (American Physiological Society, 2010)
This investigation tested the hypothesis that metabolic syndrome decreases the relative contribution of specific K(+) channels to coronary reactive hyperemia. Ca(2+)-activated (BK(Ca)), voltage-activated (K(V)), and ATP-dependent (K(ATP)) K(+) channels were investigated. Studies were conducted in anesthetized miniature Ossabaw swine fed a normal maintenance diet (11% kcal from fat) or an excess calorie atherogenic diet (43% kcal from fat, 2% cholesterol, 20% kcal from fructose) for 20 wk. The latter diet induces metabolic syndrome, increasing body weight, fasting glucose, total cholesterol, and triglyceride levels. Ischemic vasodilation was determined by the coronary flow response to a 15-s occlusion before and after cumulative administration of antagonists for BK(Ca) (penitrem A; 10 μg/kg iv), K(V) (4-aminopyridine; 0.3 mg/kg iv) and K(ATP) (glibenclamide; 1 mg/kg iv) channels. Coronary reactive hyperemia was diminished by metabolic syndrome as the repayment of flow debt was reduced ∼30% compared with lean swine. Inhibition of BK(Ca) channels had no effect on reactive hyperemia in either lean or metabolic syndrome swine. Subsequent inhibition of K(V) channels significantly reduced the repayment of flow debt (∼25%) in both lean and metabolic syndrome swine. Additional blockade of K(ATP) channels further diminished (∼45%) the repayment of flow debt in lean but not metabolic syndrome swine. These data indicate that the metabolic syndrome impairs coronary vasodilation in response to cardiac ischemia via reductions in the contribution of K(+) channels to reactive hyperemia.